The Central American Dry Corridor in a Historical Perspective - Díaz Bolaños, Ronald E. (2019)
This article addresses through a literature review the economic and social processes developed in the Central American Dry Corridor located on the Pacific slope of Central America. Since ancient times, this territory has been inhabited by human populations that adapted to their particular climatic conditions. This geographic context favored the process of European conquest and colonization that led to livestock and other productive activities. From the 19th century, with the emergence of national states, these lands were incorporated into the capitalist agro-export economic model that consolidated agricultural development. The objective of this work is to analyze the socioeconomic processes present in the CADC from the beginning of the human presence until the middle of the 20th century.